Bifurcation and Degradation of Geomaterials in the New Millennium Proceedings of the 10th International Workshop on Bifurcation and Degradation in Geomaterials - Chau, Kam-Tim.; Zhao, Jidong; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book contains contributions to the 10th International Workshop on Bifurcation and Degradation in Geomaterials held in Hong Kong, May 28-30, 2014. This event marks the silver Jubilee anniversary of an international conference series dedicated to the research on localization, instability, degradation and failure of geomaterials since 1988 when its first workshop was organized in Germany. This volume of book collects the latest progresses and state-of-the-art research from top researchers around the world, and covers topics including multiscale modeling, experimental characterization and theoretical analysis of various instability and degradation phenomena in geomaterials as well as their relevance to contemporary issues in engineering practice.  This book can be used as a useful reference for research students, academics and practicing engineers who are interested in the instability and degradation problems in geomechanics and geotechnical engineering.  .
Simulations of shear zones and cracks in engineering materials using extended Finite Element Method -- Discrete modelling of micro-structural phenomena in granular shear zones -- Modelling hydromechanical dilation geomaterial - cavitation and localization -- Fabric evolution and its effect on strain localization in sand -- Micro-mechanical observations of strain localization in granular soils during simple shear loading -- Grainsize evolution in open systems -- Numerical modeling of failure process in cohesive geomaterials -- Hydromechanical modelling of an initial boundary value problem: Studies of non-uniqueness with a second gradient continuum -- A FE² model for hydro-mechanical coupling -- Numerical simulation and length scale calibration of micropolar hypoplastic model -- Micromechanical analysis of second order work in granular media -- Stability and bifurcation in reinforced boreholes -- Shear banding in torsion shear tests on cross-anisotropic deposits of fine Nevada sand -- Effects of flooding on crushable sand -- Numerical analysis of 1D seepage failure process of sandy materials by CWENO method -- Mechanisms of deformation in porous rocks at the grain scale -- The influence of fines content on the onset of instability and critical state line of silty sand -- A multiscale investigation of strain localization in cohesionless sand -- The effect of rotational degrees of freedom on the formation of deformation patterns in granular materials using digital image correlation -- Stick-slip motion and the associated frictional instability caused by vertical oscillations -- Investigation of direct shear interface test using micro-polar continuum approach -- Energy criterion of in-plane fracture propagation in geomaterials with rotating particles -- Dynamic instability in geomaterials associated with the presence of negative stiffness elements -- Numerical modeling of particle breaking process in granular materials: compaction and evolution of size distribution -- Onset of strain localization in unsaturated soils subjected to constant water content loading -- Double-scale assessment of micro-mechanics based constitutive models for granular materials undergoing mechanical degradation -- Hypoplastic constitutive modelling of grain damage under plane shearing -- Hierarchy of failure indicators in the failure analysis of geomaterials -- Static liquefaction of granular soils: the role of grain shape and size -- Static liquefaction and instability in granular media subjected to monotonic loading – A micromechanical investigation -- Capillary effect on critical length of force chains in partially saturated granular materials within the pendular regime -- Study on the initiation of strain localization in soils by 3D non-coaxial plasticity -- Micromechanics-based constitutive modeling and DEM simulation of localized failure in soil -- Thermally induced deformation and failure in shale under drained and undrained heating -- Instability of dissociation process of methane hydrate bearing soil -- Development of image analysis tools to evaluate in-situ evolution of the grain size distribution in sand subjected to breakage -- FEMÍDEM multi-scale analysis of boundary value problems involving strain localization -- Evolution of packing structure in cyclic mobility and post-liquefaction of granular soils -- Experimental versus finite element approach to study scale dependent features in granular materials’ stress and deformation fields -- Onset of strain localization in fiber reinforced composites subjected to plane stress loading -- Using shear strain localisation to model the fracturing around gallery in unsaturated Callovo-Oxfordian claystone -- Experimental study on the behavior of a plasticine material -- Thermodynamic analysis of instability in unsaturated soils -- Plastic deformations in granular materials with rotation of principal stress axes -- A framework to assess the controllability of wetting on unsaturated collapsible soils -- Model tensile cracking in soil with coupled meshless-FEM method -- Quantitative observation of strain localisation in a partially saturated triaxial specimen using microfocus X-ray CT with image analysis -- Simple modeling of time-dependent behavior for structured soils -- The role of microstructure in the liquefaction mechanism -- Dense granular flows: structure and microscopic origins of internal friction -- Dynamic analysis of strain localization in water-saturated elasto-viscoplastic material -- Micromechanical modelling of granular materials through fabric and coordination number anisotropies -- Repetitive compression tests on a carbonate sand -- The evolution of shear bands in sand: Numerical investigations based on an elasto-plastic Cosserat continuum approach.
Keywords: Ocean engineering; Geotechnical engineering; Offshore Engineering; Geotechnical Engineering & Applied Earth Sciences